Modelling, fabrication, and characterization of memristor for mitigating the sneak path current in a nano-crossbar memory array - M, Arya Lekshmi (2022)
The semiconductor industry looks ahead to Resistive random-access memory (RRAM), (alternatively known as memristor), a promising emerging non-volatile memory technology that can be developed to become a solution for high-density data storage problems. However, the formation of crossbar arrays with RRAM devices results in the origin of leakage current from the unselected cells known as sneak path current, which is identified as the major hindrance to the development of RRAM as it adversely affects data integrity. Among various prevailing solutions to mitigate sneak path current, the effective methods are incorporating a selector switch in association with the memory device to form one selector-one resistor (1S1R) configuration and complementary switching (CRS) devices formed by back-to-back connected RRAMs.